PerfuPul—A Versatile Perfusable Platform to Assess Permeability and Barrier Function of Air Exposed Pulmonary Epithelia - Carius, Patrick; Dubois, Aurélie; Ajdarirad, Morvarid; Artzy-Schnirman, Arbel; Sznitman, Josué; Schneider-Daum, Nicole; Lehr, Claus-Michael (Frontiers in Bioengineering and Biotechnology, 2021)
Complex in vitro models, especially those based on human cells and tissues, may successfully reduce or even replace animal models within pre-clinical development of orally inhaled drug products. Microfluidic lung-on-chips are regarded as especially promising models since they allow the culture of lung specific cell types under physiological stimuli including perfusion and air liquid interface (ALI) conditions within a precisely controlled in vitro environment. Currently, though, such models are not available to a broad user community given their need for sophisticated microfabrication techniques. They further require systematic comparison to well-based filter supports, in analogy to traditional Transwells®. We here present a versatile perfusable platform that combines the advantages of well-based filter supports with the benefits of perfusion, to assess barrier permeability of and aerosol deposition on ALI cultured pulmonary epithelial cells. The platform as well as the required technical accessories can be reproduced via a detailed step-by-step protocol and implemented in typical bio-/ pharmaceutical laboratories without specific expertise in microfabrication methods nor the need to buy costly specialized equipment. Calu-3 cells cultured under liquid covered conditions (LCC) inside the platform showed similar development of transepithelial electrical resistance (TEER) over a period of 14 days as cells cultured on a traditional Transwell®. By using a customized deposition chamber, fluorescein sodium was nebulized via a clinically relevant Aerogen® Solo nebulizer onto Calu-3 cells cultured under ALI conditions within the platform. This not only allowed to analyze the transport of fluorescein sodium after ALI deposition under perfusion, but also to compare it to transport under traditional static conditions.